Modeling of GP(I) zone formation during quench in an industrial AA7449 75 mm thick plate. (15th December 2016) - Schloth, P.; Deschamps, A.; Gandin, Ch.-A.; Drezet, J.-M.
Abstract: The GP(I) zone formation during quench is simulated in an industrial Aluminum alloy AA7449 75 mm thick plate by using a multi-class precipitation model. For this purpose, results of in situ SAXS experiments are reported. A methodology is presented that takes advantage of the collected data to derive i - a thermodynamic description for GP(I) zones from reversion heat treatments by using a solubility product and ii - the influence of excess vacancies on diffusion coefficients. This approach allows reproducing reasonably well the GP(I) zone formation measured during rapid cooling. Further, the simulated as-quenched surface yield strength compares well with experimental results reported in the literature. Graphical abstract: